2019
DOI: 10.1016/j.cell.2019.02.038
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Aging: A Vertebrate Perspective

Abstract: Aging negatively impacts vitality and health. Many genetic pathways that regulate aging were discovered in invertebrates. However, the genetics of aging is more complex in vertebrates because of their specialized systems. This Review discusses advances in the genetic regulation of aging in vertebrates from work in mice, humans, and organisms with exceptional lifespans. We highlight challenges for the future, including sex-dependent differences in lifespan and the interplay between genes and environment. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
178
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(182 citation statements)
references
References 186 publications
2
178
0
2
Order By: Relevance
“…FOXOs play a role in cancer [43], diabetes [44,45] and longevity [46,47], as well as other disease-related processes.…”
Section: Foxo Functionmentioning
confidence: 99%
“…FOXOs play a role in cancer [43], diabetes [44,45] and longevity [46,47], as well as other disease-related processes.…”
Section: Foxo Functionmentioning
confidence: 99%
“…Investigation of organisms that exhibit extreme longevity, however, may also hold unique promise for identification of anti-ageing defences obtained through evolution. Our own species is an obvious candidate, and comparison among human populations and among individuals within populations-including, for instance, centenarians-has shed tremendous light on genetic and environmental effects on longevity [9]. Some species of bivalves have extreme lifespans-the ocean quahog ( Arctica islandica ), for instance, is notable for living up to 507 years [10].…”
Section: Models For Human Health and Ageingmentioning
confidence: 99%
“…Aging is a complex, multifarious process characterized by changes such as stem cell exhaustion, mitochondrial dysfunction, impaired immune function, reduced autophagy, epigenetic alterations, accumulation of somatic and mitochondrial DNA mutations, aberrant intercellular communication, loss of telomeres, altered nutrient sensing, and impaired protein homeostasis (Lopez‐Otin, Blasco, Partridge, Serrano, & Kroemer, ; Singh, Demmitt, Nath, & Brunet, ). A large portion of our current, limited understanding of what causes aging comes from lifespan studies in short‐lived model organisms.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of research showing that caloric restriction improves health and survival in rhesus monkeys (Mattison et al, ), little aging work has been done in longer‐lived organisms. The bulk of our understanding regarding aging comes from genetic experiments in model organisms (Singh et al, ), and we do not yet know how similar or dissimilar human aging is. For example, genome‐wide association studies searching for longevity‐related variants have found a lack of association with many genes known to extend lifespan in simpler animals (de Magalhaes, ).…”
Section: Introductionmentioning
confidence: 99%